A hybrid method to quantify household urban agriculture gardening: Implications for sustainable and equitable food action planning - Ramaswami, Anu; Boyer, Dana; Nixon, Peter; Jelinski, Nic (Frontiers in Sustainable Food Systems, 2022)
Urban food action plans seek quantitative data on household agriculture gardening, traditionally difficult to quantify rapidly, as well as data on inequality to explore potential to improve equitable access to fresh vegetables through household agriculture. This paper presents a novel Hybrid Field Survey (HFS) method, combining ground surveys with satellite imagery to quantify the prevalence and area of household agriculture gardens, as well as inequality by neighborhood income. We test the method in Minneapolis and St. Paul, Minnesota, (Twin Cities), USA, analyzing presence/absence (prevalence) and size of agriculture gardens across a total of 15,000 households in 2017 and repeated in 2020 (during Covid-19). In 2017, the overall mean frequency of household agricultural gardening was 5.0%, with significant differences (2.7% vs 7.0%) across low- versus high-income neighborhoods. The citywide median area per agriculture garden size was 14.6 m2 with greater size (19.8m2 vs 11.6m2) in low- versus in high-income neighborhoods, respectively. Across all income groups, gardening area was a small fraction of the yard area, suggesting little land availability constraints. Measurements in summer 2020 during COVID-19, found the method sensitive over time, showing an overall 60% increase in the prevalence of household agriculture with low income-neighborhoods increasing rates from 3% to 5%. Overall, the method can inform aggregate production potential and inequality in household agriculture.